Building Protein‐Protein and Protein‐Glycosaminoglycan Interaction Networks Using MatrixDB, the Extracellular Matrix Interaction Database. Issue 4 (1st April 2021) - Berthollier, Coline; Vallet, Sylvain D.; Deniaud, Madeline; Clerc, Olivier; Ricard‐Blum, Sylvie
Abstract: The interaction database MatrixDB reports protein‐protein and protein‐glycosaminoglycan interactions in human, mammalian, and model organisms, involving at least one extracellular matrix (ECM) constituent, namely full‐length proteins, ECM multimeric proteins considered as stable complexes, proteoglycans, glycosaminoglycans (GAGs), and bioactive fragments called matricryptins, which are released upon limited proteolysis of ECM proteins. The current version of MatrixDB (as of October 2020) contains 106, 543 experimentally supported interactions, with all types of biomolecules combined. MatrixDB is the only database focusing on the curation of ECM protein and GAG interactions. The iNavigator integrated in MatrixDB allows users to build interaction networks online and to filter them according to expression data, quantitative proteomics data, or interaction detection methods. MatrixDB belongs to the International Molecular Exchange (IMEx) consortium, and uses its curation rules to capture interaction data, which are available in standardized exchange formats according to the Human Proteome Organization—Proteomics Standards Initiative (HUPO‐PSI). © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Browse MatrixDB Basic Protocol 2 : Create a list of biomolecules of interest to build interaction networks Basic Protocol 3 : Build and export interaction networks of selected biomolecules using the iNavigator Basic Protocol 4 : Build specific interaction networks using the iNavigator widgets Basic Protocol 5 : Generate 3D models of glycosaminoglycan oligosaccharides using the GAG Builder tool